Intervención del terapista respiratorio en paciente femenino de 40 años con bronquiectasias. - Trejo Ramirez, Diego Jesus (2022)
Bronchiectasis is a disease in which the major airways of the lungs are damaged. This causes the airways to widen permanently. Bronchiectasis can occur at birth or in childhood or develop later in life. Bronchiectasis can be caused by a previous disease in the lung (pneumonia, tuberculosis, radiotherapy), be associated with chronic respiratory diseases (COPD, asthma, bronchial stenosis) or even general diseases such as cystic fibrosis, immunodeficiencies or inflammatory bowel disease. Bronchiectasis can be caused by a previous disease in the lung (pneumonia, tuberculosis, radiotherapy), be associated with chronic respiratory diseases (COPD, asthma, bronchial stenosis) or even general diseases such as cystic fibrosis, immunodeficiencies or inflammatory bowel disease. Bronchiectasis can develop from an infection or a medical disorder, such as pneumonia and cystic fibrosis. The mucosa accumulates and allows the proliferation of bacteria, which causes frequent infections. Symptoms include daily coughing for months or years, and production of large amounts of phlegm every day. Treatment may include physical therapy and medications, such as antibiotics and drugs to loosen the mucosa.